Peritoneal Carcinomatosis: Current State of the Art and Schools of Thought - Sh. Kh. Gantsev; M. V. Zabelin; K. Sh. Gantsev; A. A. Izmailov; Sh. R. Kzyrgalin (Креативная хирургия и онкология, 2021)
Peritoneal carcinomatosis (PC) is a global challenge of modern oncology representing the most unfavourable scenario in diverse-locality tumourisation. Despite certain attention by the oncological community, the management of PC patients is currently palliative, which weakly promotes research into the basic principles of this morbidity. This literature review attempts to comprehensively cover the PC problematic from a global perspective and presents a key evidence on the world schools of thought in this area. Briefly taking, peritoneal carcinomatosis is viewed today as a local process in the conventional implantation theory, which imposes a locoregional character on all current or emerging therapies, such as cytoreductive surgery and hyperthermic intraperitoneal chemotherapy. Their inadequate efficacy is largely due to pronounced gaps in our understanding of PC logistics and signalling. PSOGI is a key organisation for centralising the specialty effort in peritoneal carcinomatosis. Despite its global geography and approach to PC discussion, a multitude of scientific questions remain unanswered impeding the establishment of novel effective therapies. The seven countries that nurtured distinguished schools of thought in PC studies are the USA, UK, Japan, China, Italy, France and Germany. Taking peritoneal carcinomatosis in a global perspective, an insufficient attention to its problematic in Russia should be addressed. The founding and fostering of national PC institutions will benefit cancer patients and progress in oncological science.